Enhancing Scientific Conceptualization and Responsibility in Deaf Learners Through Technology-Enhanced Learning: Development and Validation of a Digital Fun Thinkers Tool - Agustiana, I Gusti Ayu Tri; Tika, I Nyoman; Sukmana, Adrianus I Wayan Ilia Yuda; Astawan, I Gede; Pahmi, Samsul; Bayuaji, Luhur (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study aims to design, develop, and validate a culturally adapted Digital Fun Thinkers learning tool to enhance scientific conceptualization and learning responsibility among deaf and hard-of-hearing elementary students in Bengkala Village, Bali, Indonesia. Methodology: This study employed the ADDIE instructional design model and a one-group pretest–posttest quasi-experimental design. The Digital Fun Thinkers tool was developed as an interactive multimedia application. Data were analyzed using Aiken’s V, paired-sample t-test, and normalized gain (N-Gain). Main Findings: Expert validation indicated high validity (media experts: V = 0.9583; material experts: V = 0.9350) and very practical use (user satisfaction = 81.39%). Students’ scientific conceptualization improved significantly (t = -37.997, p < 0.001; N-Gain = 0.7338, large effect). Learning responsibility averaged 66.28 (very high category). Novelty/Originality of this study: This study introduces a culturally grounded digital learning tool integrating Kata Kolok sign language, gamified features, and local scientific contexts for deaf learners. It advances inclusive science education by providing empirically validated, technology-enhanced resources tailored to marginalized DHH communities in rural settings.